The molecular traits of food allergens - Bartuzi, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Allergens are defined as environmental agents that induce IgE-mediated immediate hypersensitivity reactions following inhalation, ingestion or injection. Purified allergens are named using the systematic nomenclature of the Allergen Nomenclature Sub-Committee of the World Health Organization and International Union of Immunological Societies. Major allergens may have special aerobiological properties and allergenic structures. Allergens are derived from proteins with a variety of biological functions, including proteases, ligand-binding proteins, structural proteins, pathogenesis-related proteins, lipid transfer proteins, profilins, and calcium-binding proteins. Biological function, such as the proteolytic enzyme allergens of dust mites, might directly influence the development of IgE responses and might initiate inflammatory responses in the lung that are associated with asthma. Intrinsic structural or biological properties might also influence the extent to which allergens persist in indoor and outdoor environments or retain their allergenicity in the digestive tract. Structural biology and proteomics define recombinant allergen targets for diagnostic and therapeutic purposes and identify motifs, patterns, and structures of immunological significance. The development of any new treatment will require in-depth structural and biochemical knowledge of the food allergens that precipitate the clinical symptoms.